THE ROLE OF MEDIC AND BIOLOGICAL FACTORS IN LANGUAGE DEVELOPMENT IN SCHOOLCHILDREN: REVIEW OF CURRENT RESEARCH - Chernov, Dmitry Nikolayevich (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Purpose. The article is devoted to analysis of contemporary research of pre-, peri- and neonatal factors that contributes to individual differences in language abilities at school age in correlation with features of the relationship of the child with the closest social environment, which can modulate the contribution of medic and biological factors in language development of schoolchildren. Methodology. A comparative meta-analysis of foreign and domestic studies which were performed over the last 20 years is conducted. The works which were included in the database PabMed, Web of Science, Scopus и elibrary.ru are analyzed. Results. Teratogenic factors, prematurity and low birth weight can have long-term impact on the development of language abilities in children up to secondary school age. The experimental data do not allow to make a definite conclusion about the presence of sex differences in language development at school age. Discrepancies are observed in the results concerning the value of the contribution of medic and biological factors in child language development depending on research approaches. Positive parent-child relationship plays a significant role in compensation of the negative effects of pre-, peri -, and neonatal factors in the language development in schoolchildren. Practical implications. The results of meta-analysis can be used to create programs of prevention and correction of formation of the language abilities of schoolchildren with regard to the peculiarities of their development in pre-, peri- and neonatal periods of ontogenesis. The central importance must be given to the role of parent-child relationships in mediation of the contribution of medic and biological factors in the subsequent language development in children.